2012
DOI: 10.1523/jneurosci.5685-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

A Temporal Bottleneck in the Language Comprehension Network

Abstract: Humans can understand spoken or written sentences presented at extremely fast rates of ϳ400 wpm, far exceeding the normal speech rate (ϳ150 wpm). How does the brain cope with speeded language? And what processing bottlenecks eventually make language incomprehensible above a certain presentation rate? We used time-resolved fMRI to probe the brain responses to spoken and written sentences presented at five compression rates, ranging from intelligible (60 -100% of the natural duration) to challenging (40%) and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 70 publications
11
96
1
1
Order By: Relevance
“…This finding converges with increasing evidence that visuomotor coordination and motor representation are modulated by neurons within the temporal region (Tankus and Fried, 2012) and that cognitive processing speed is associated with temporal cortical structural integrity (Turken et al, 2008). Moreover, some data suggest that higher stages of language processing operate at a fixed speed and could theoretically impose a 'temporal bottleneck' on language functions (Vagharchakian et al, 2012). In this regard, Takeuchi et al, (2011) demonstrated that processing speed training was associated with both structural and functional changes in temporal regions.…”
Section: Discussionsupporting
confidence: 78%
“…This finding converges with increasing evidence that visuomotor coordination and motor representation are modulated by neurons within the temporal region (Tankus and Fried, 2012) and that cognitive processing speed is associated with temporal cortical structural integrity (Turken et al, 2008). Moreover, some data suggest that higher stages of language processing operate at a fixed speed and could theoretically impose a 'temporal bottleneck' on language functions (Vagharchakian et al, 2012). In this regard, Takeuchi et al, (2011) demonstrated that processing speed training was associated with both structural and functional changes in temporal regions.…”
Section: Discussionsupporting
confidence: 78%
“…Altogether, the putative representation of open nodes was mostly confined to classical areas of the sentence-processing network identified with fMRI (14,15), namely the STS, IFG, dorsal precentral/prefrontal cortex in the vicinity of area 55b (37), and the dorsomedial surface of the frontal lobe. A previous fMRI study suggested that this area may maintain a linguistic buffer (38), which is consistent with a representation of open nodes.…”
Section: Resultssupporting
confidence: 64%
“…Previous studies reported that neural responses of only a few areas within the occipito-temporal cortex increased linearly with visibility or presentation duration of written input (Ben-Shachar et al, 2007;Price and Friston, 1997;Vagharchakian et al, 2012). Here, we found a linear activation pattern in all of the areas identified in the network described above.…”
Section: Stimulus-driven Activation Of Orthographic Phonological Andsupporting
confidence: 75%
“…Yet, given the existence of functional and anatomical connections between the visual and auditory systems (Booth et al, 2002;Thiebaut De Schotten et al, 2014;Vagharchakian et al, 2012;Yeatman et al, 2011), it is likely that processing written words also induces activation in the spoken language system, although to a lesser extent. To further examine how the spoken language system is influenced by written words' visibility and task demand, we restricted our analyses to the cortical areas that process acoustic, phonological and semantic contents of spoken sentences, using the subject-specific approach proposed by NietoCastañón and Fedorenko (2012).…”
mentioning
confidence: 99%